Pencegahan Edukasi CyaberBullying dalam Pandangan Islam - Muslima (JKA, 2024)
The development of information and communication technology, especially in the digital age, has a significant impact on social interaction but poses serious challenges, such as an increase in cyberbullying incidents. The research aims to integrate Islamic values into a preventive educational approach to cyberbullying, acknowledging that Islam not only teaches spiritual values, but also provides an ethical basis to address these challenges. The Islamic perspective on individual protection emphasizes respect for human rights, the right to privacy, and norms of behaviour that promote healthy social life. Research understands the definition and characteristics of cyberbullying as the basis for designing holistic prevention strategies in line with human values. Through International Community Commitment (ICC), research involves lecturers, students, and stakeholders to disseminate knowledge and raise awareness, especially about the role of academics and school leaders in the digital age. The results of the evaluation showed the positive impact and active participation of the public, contributing to the solution of problems and self-development of the community. This research has made a real contribution to addressing the challenges of cyberbullying, creating a safer digital environment and in line with the principles of Islamic justice.